Design and fabrication of 3D‐printed planar Fresnel zone plate lens. Issue 10 (1st May 2016) - Zhang, S.
Abstract : 3D‐printing has been used for rapidly prototyping a low‐cost and light‐weight dielectric Fresnel zone plate lens. This lens was comprised of four dielectric zones and they were fabricated in one process with the tailored permittivities. Measurements show that this lens provides 7.3–12.8 dB gain enhancement over the frequency band from 8 to 12 GHz.